2022
DOI: 10.1186/s12978-022-01430-w
|View full text |Cite
|
Sign up to set email alerts
|

Doctors’ experiences providing sexual and reproductive health care at Catholic Hospitals in the conflict-affected North-West region of Cameroon: a qualitative study

Abstract: Background Sexual and reproductive health (SRH) care services are essential to improving the lives of women and achieving the Sustainable Development Goals. In Cameroon, the Catholic Church is one the largest non-governmental suppliers of health care, but its role in providing SRH care is restricted by religious norms. Methods This study explored doctors’ experiences and perceptions of providing SRH care at Catholic hospitals in a conflict-affected… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…A wide range of study designs and methods were used across the papers, with both qualitative and quantitative studies well represented. Twenty-six papers were quantitative evaluations , 17 were qualitative [44][45][46][47][48][49][50][51][52][53][54][55][56][57][58][59][60], and 26 used mixed methods . Within the quantitative evaluations, 15 were observational, while five were quasi-experimental, five were randomized controlled trials, and one was an economic evaluation.…”
Section: Resultsmentioning
confidence: 99%
“…A wide range of study designs and methods were used across the papers, with both qualitative and quantitative studies well represented. Twenty-six papers were quantitative evaluations , 17 were qualitative [44][45][46][47][48][49][50][51][52][53][54][55][56][57][58][59][60], and 26 used mixed methods . Within the quantitative evaluations, 15 were observational, while five were quasi-experimental, five were randomized controlled trials, and one was an economic evaluation.…”
Section: Resultsmentioning
confidence: 99%
“…Similarly, Haddison et al [ 29 ] study, which compared the utilization of reproductive services before (2016–2017) and during (2018) the armed conflict in the South West region of Cameroon, found that the utilization of reproductive services (deliveries attended by skilled birth attendants, and attendance at antenatal care) deteriorated during the armed conflict compared to the before the armed conflict. Awasom-Fru et al’s [ 30 ] study among doctors at a Catholic Hospital in the North West region of Cameroon found that adherence to Catholic rules (such as a ban on advice and prescription of modern contraceptives within the hospital) and perception of fear within the hospital environment limited the accessibility of SRHS to hospital clients, including adolescents.…”
Section: Introductionmentioning
confidence: 99%